Financial Feasibility Analysis Of Oyster Mushroom Cultivation Business : Case Study of Tiga Putra Farm Oyster Mushroom Cultivation Business in Anduonohu Village, Poasia District, Kendari City - Martin Prayoga; R. Marsuki Iswandi; Abdul Gafaruddin (International journal of technology and education research, 2025)
This study aims to (1) analyze the financial feasibility of Tiga Putra Farm oyster mushroom farming in Anduonohu Village, Poasia District, Kendari City and (2) determine the sensitivity of the financial feasibility of Tiga Putra Farm oyster mushroom cultivation in Anduonohu Village, Poasia District, Kendari City. This research uses a case study method in the Tiga Putra Farm oyster mushroom cultivation in Anduonohu Village, Poasia District, Kendari City with the business owner being the informant in the study. The results showed that the financial aspect obtained an NPV value of Rp 37,525,391.33 with a discount factor rate of 14%, Net B/C of 3.37 and an IRR value of 55.89% and a Payback Period is 2.0 or 3 years and 3 months. This business is declared financially feasible. In addition, based on the calculation of sensitivity analysis carried out in three simulations, the business is still feasible to run even though in the first simulation, there was a decrease in oyster mushroom production by 7.45% and in the second simulation, an increase in operating costs by 6.16% and in the third simulation, for the condition of decreasing oyster mushroom production by 7.45% and increasing operating costs by 6.16% simultaneously, Tiga Putra Farm's oyster mushroom farming is still feasible to run.